2018
DOI: 10.1093/ndt/gfx365
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in kidney transplantation: a viewpoint from the Descartes advisory board*

Abstract: Transplantation medicine is a rapidly evolving field. Keeping afloat of the published literature to offer the best clinical care to our patients is a daunting task. As part of its educational mission, the Descartes advisory board identified seven topics in kidney transplantation where there has been substantial progresses over the last years: kidney allocation within Eurotransplant; kidney exchange strategies; kidney machine perfusion strategies; the changing landscape of anti-human leukocyte antigen (HLA) ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 77 publications
(82 reference statements)
0
37
0
Order By: Relevance
“…The use and optimisation of protocols in different dynamic MP technologies for abdominal organ preservation (liver, kidney, and pancreas) have been extensively studied in the last decades in single or multi-centre randomised controlled trials (RCTs) [1] and different preclinical human and animal models. In order to expand the current donor pool and match the waitlist demand, there has been an increase in organ retrieval from different donors, such as donation after brain death (DBD), donation after circulatory death (DCD), and extended criteria donor (ECD) [2]. In particular, ECD grafts are associated with poorer transplantation outcomes and there is controversy in terms of greater overall economic costs [3].…”
Section: Current State Of Abdominal Transplantation (Liver Kidneys mentioning
confidence: 99%
“…The use and optimisation of protocols in different dynamic MP technologies for abdominal organ preservation (liver, kidney, and pancreas) have been extensively studied in the last decades in single or multi-centre randomised controlled trials (RCTs) [1] and different preclinical human and animal models. In order to expand the current donor pool and match the waitlist demand, there has been an increase in organ retrieval from different donors, such as donation after brain death (DBD), donation after circulatory death (DCD), and extended criteria donor (ECD) [2]. In particular, ECD grafts are associated with poorer transplantation outcomes and there is controversy in terms of greater overall economic costs [3].…”
Section: Current State Of Abdominal Transplantation (Liver Kidneys mentioning
confidence: 99%
“…In the wake of the redesign of the US Kidney Allocation System in 2014, there has been growing interest globally surrounding the role of recipient/organ longevity matching in kidney transplant allocation . After validation of a modified version of the US KDPI, Australia began reporting this score with all kidney offers despite it not being incorporated into local allocation algorithms and without changes to the clinical information available to accepting clinicians, offering an opportunity to assess for potential labeling effects associated with the reporting of this organ quality index.…”
Section: Discussionmentioning
confidence: 99%
“…the role of recipient/organ longevity matching in kidney transplant allocation. [9][10][11] After validation of a modified version of the US KDPI, 3 Australia began reporting this score with all kidney offers despite it not being incorporated into local allocation algorithms and without changes to the clinical information available to accepting clinicians, offering an opportunity to assess for potential labeling effects associated with the reporting of this organ quality index. We found that KDPI reporting has been associated with a 45% increase in the number of organ offer declines for higher-risk (KDPI > 80%) kidneys without a significant increase in the rate Our results suggest there is at a degree of labeling effect in KDPI reporting, given that the component donor information was available before the introduction of KDPI reporting.…”
Section: Changes In Recipient Characteristicsmentioning
confidence: 99%
“…DCD outcomes over time presumably involves a complex interplay of factors that includes optimized surgical procedures and immunosuppressive regimens, altered organ preservation techniques, and enhanced transport logistics [15][16][17][18][19]. Certainly, a significant impact has been the profound reduction in cold ischaemic time [16,20].…”
Section: Plos Onementioning
confidence: 99%